PERTIMBANGAN HAKIM DALAM MENETAPKAN DISPENSASI PERKAWINAN MENURUT UU NO 16 TAHUN 2019 PERUBAHAN ATAS UU NO 1 TAHUN 1974 TENTANG PERKAWINAN (ANALISIS PERKARA NO.15 Pdt.P/DI PENGADILAN AGAMA BINJAI ) - Pradana, Ghifari; Nasution, Abdul Halim (Program Studi Hukum Keluarga Islam Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2025)
Early marriage continues to pose significant legal and social challenges in Indonesia, despite regulatory reforms introduced by Law No. 16 of 2019, which raised the minimum legal age of marriage to 19 years for both men and women. This reform has led to a marked increase in applications for marriage dispensation submitted to the Religious Courts, indicating a persistent gap between statutory norms and social realities. This study examines judicial considerations in Case No. 15/Pdt.P/2024/PA.Bji at the Binjai Religious Court. A qualitative approach is employed to explore the social, psychological, and cultural factors influencing judicial decision-making. The findings reveal that judges take into account psychological readiness, social pressures, and the principle of child protection in rendering their decisions. The study underscores the central role of judges as interpreters of substantive law amid complex social dilemmas and recommends strengthening support systems—such as the involvement of psychologists and enhanced public education—to prevent child marriage.